Ferroptosis and Alzheimer’s disease: a new insight into neurodegeneration - Quan, Youfang; Liu, Hongwei; Zhang, Minheng; Li, Meng; He, Bo; Wang, Ke; Huang, Xuewen; Zhou, Shengyang; Han, Zhongyu; Fan, Haixia (Frontiers in Immunology, 2026)
Alzheimer’s disease (AD), a chronic and progressive neurodegenerative disorder, poses a significant threat to the health of the aging population. The pathological hallmarks of AD include the accumulation of amyloid-β (Aβ) plaques and neurofibrillary tangles (NFTs) within the brain. While substantial neuronal loss has been consistently observed in AD, the precise mechanisms underlying neuronal elimination remain incompletely understood. As a distinct form of regulated cell death, the contribution of ferroptosis to AD pathogenesis and progression warrants further investigation. This review critically examines the amyloid cascade hypothesis within the context of AD, with particular emphasis on the molecular signatures of ferroptosis and their contributions to canonical AD pathogenesis and cognitive decline. We aim to provide an updated perspective on AD etiopathogenesis. Furthermore, we synthesize current therapeutic strategies targeting ferroptosis inhibition in AD, highlighting recent advances that hold significant implications for guiding present and future translational efforts.